Pregnant Drug Users: Scapegoats of Reagan/Bush And Clinton-Era Economics - Murphy, Sheigla (Social justice, 2001)
A study was conducted to examine the ways in which pregnant drug users in the San Francisco Bay Area, California, experienced, coped with, and protected themselves from growing stigmatization, abuse, and punishment during a period of fiscal retrenchment of government assistance programs running from the Reagan to the Clinton era. These funding decisions created barriers and denied access to cost-effective services that would allow pregnant drug users with limited means to improve their lives. Findings reveal that such women were forced to find alternative resources and to construct survival strategies that included drug use, compromising their ability to care for themselves and their children.